Entrepreneurial ways of designing and designerly ways of entrepreneuring: Exploring the relationship between design thinking and effectuation theory - Klenner, Nico Florian; Gemser, Gerda; Karpen, Ingo Oswald (The Journal of product innovation management, 2022)
Scholars have suggested that design thinking and effectuation theory may enrich each other. However, to date, we lack deeper theorizing and empirical evidence to further advance this valuable discourse for the benefit of innovation management. Our qualitative study draws on 41 in‐depth interviews with Australian designer‐founders, with the aim to provide a theoretical perspective on and empirical insights into the relationship between the behavioral practices of design thinking and the cognitive principles of effectuation. The contributions are twofold. First, our study explains how design thinking practices enable designer‐founders to enact the cognitive principles of effectuation. Uncovering these "entrepreneurial ways of designing" provides an explanation for the effectiveness of design thinking for entrepreneurial innovation and new venture creation. Second, our study sheds light on the ways in which designer‐founders interpret effectuation principles through the professional values and norms embodied in design thinking. These "designerly ways of entrepreneuring" resemble particular, normative interpretations of effectual action. By doing so, our study offers empirical substantiation and theoretical elaboration of the ways in which design thinking functions as an approach for entrepreneurial innovation and new venture creation. Through shedding light on the "entrepreneurial ways of designing" and "designerly ways of entrepreneuring" exhibited by designer‐founders, our research reveals the reciprocal relationship between design thinking and effectuation theory.